Wearable devices in education: Trends and challenges - Oliveira, Lino (2016)
With the exponential growth of smart devices (mobile and wearable) in recent years and the combination of computing technologies with Internet connectivity has shifted from our offices and homes for our pockets. Much of the optimism for the future of wearable technology is based on the belief that wearable devices will become ubiquitous in the future due to increased connectivity, improved usability, reduced costs, increased reliability, and the battery lifetime will increase. This new technology enables a new generation of mobile learning design courses. In this context, in order for educators to harness the pedagogical opportunities of wearable technologies it is crucial for them to develop an understanding of their trends and challenges. However, However, there is considerable literature to investigate the development and use of wearable technologies in several areas, but very scarce in the education field. This paper focuses on the presentation of the trends and challenges that wearable devices represent for education.